Adenine nucleotide loss in the skeletal muscles during exercise in chronic obstructive pulmonary disease. Issue 11 (29th July 2005) - Steiner, M C; Evans, R; Deacon, S J; Singh, S J; Patel, P; Fox, J; Greenhaff, P L; Morgan, M D L
Abstract : Background: Skeletal muscle adenine nucleotide loss has been associated with fatigue during high intensity exercise in healthy subjects but has not been studied in patients with chronic obstructive pulmonary disease (COPD). Changes in adenine nucleotides and other metabolites in the skeletal muscles were measured in patients with COPD and age matched healthy volunteers by obtaining biopsy samples from the quadriceps muscle at rest and following a standardised exercise challenge. Methods: Eighteen patients with COPD (mean (SD) forced expiratory volume in 1 second 38.1 (16.8)%) and eight age matched healthy controls were studied. Biopsy samples were taken from the vastus lateralis muscle at rest and immediately after a 5 minute constant workload cycle test performed at 80% peak work achieved during a maximal incremental cycle test performed previously. Results: The absolute workload at which exercise was performed was substantially lower in the COPD group than in the controls (56.7 (15.9) W v 143.2 (26.3) W, p<0.01). Despite this, there was a significant loss of adenosine triphosphate (mean change 4.3 (95% CI −7.0 to −1.6), p<0.01) and accumulation of inosine monophosphate (2.03 (95% CI 0.64 to 3.42), p<0.01) during exercise in the COPD group that was similar to the control group (−4.8 (95% CI −9.7 to 0.08), p = 0.053 and 1.6 (95% CI 0.42 to 2.79), p<0.01, respectively). Conclusions: These findings indicate that the ATP demands of exercise were not met by resynthesis from oxidative and non-oxidative sources. This suggests that significant metabolic stress occurs in the skeletal muscles of COPD patients during whole body exercise at low absolute workloads similar to those required for activities of daily living.